Safety and Effectiveness of SEP−363856 in Schizophrenia: Results of a 6-Month, Open-Label Extension Study. (April 2021) - Correll, Christoph U.; Koblan, Kenneth S.; Hopkins, Seth C.; Kent, Justine; Cheng, Hailong; Goldman, Robert; Loebel, Antony
Abstract: Background: SEP-363856 is a novel psychotropic agent without dopamine D2 receptor occupancy. Although its mechanism of action has not been fully elucidated, preclinical data suggest that agonism at trace amine receptor 1 (TAAR1) and the serotonin 5-H1A receptor contributes to its efficacy. In a double-blind (DB), placebo-controlled study, SEP−363856 demonstrated significant efficacy in the treatment of an exacerbation of schizophrenia (Koblan et al, NEJM 2020; 82:1497–1506). We present results of a 6-month extension study whose aim was to evaluate the safety and effectiveness of longer-term treatment with SEP−363856. Method: Patients with an acute exacerbation of schizophrenia who completed a 4-week, DB, placebo-controlled, flexible-dose (50 or 75 mg) study of SEP−363856 were given the option to enroll in an extension study in which they were treated, open-label (OL), with flexible doses (25/50/75 mg/d) of SEP−363856 for 26-weeks. The primary outcomes were safety measures; effectiveness outcomes were secondary and included the PANSS total score and the Brief Negative Symptom Scale (BNSS) total score. Results: A total of 193 patients completed the 4-week DB study, and 156 (80.8%) were dosed in the OL extension study and received at least one dose of SEP−363856 (safety population). Study completer rate was 66.9%; reasons for discontinuation consisted of adverse event (11.5%), withdrawal of consent (10.2%), lack of efficacy (5.1%), and other (6.4%). 15 patients experienced an SAE: schizophrenia (n=11); acute psychosis (N=1); uterine hemorrhage and suicidal ideation (N=1 each); there were no deaths in the study. Individual AEs with an incidence =2% were schizophrenia (12.2%), headache (11.5%), insomnia (8.3%), anxiety (5.1%), somnolence (4.5%), nasopharyngitis (4.5%), nausea (3.8%), irritability (3.2%), influenza (3.2%), weight decreased (3.2%), and prolactin increased (2.6%). On movement scales, minimal mean change from OL-baseline to Week 26 occurred on the Barnes total score (−0.1), AIMS total score (0.0) and SAS score (−0.1). Mean month 6 change from DB baseline in weight was −0.3 kg. No clinically meaningful median changes were observed at week 26 in metabolic laboratory parameters (total and LDL cholesterol, triglycerides, hemoglobin A1c) or in prolactin levels. During 6 months of OL treatment, one patient had an increase in QTcF =60 msec; no patients had a QTcF interval =480 msec. Treatment with SEP−363856 was associated with significant improvement from OL baseline to week 26 in PANSS total score (−22.6) and BNSS total score (−11.3). Conclusion: Treatment with SEP−363856 was associated with continued improvement from open-label baseline in the PANSS total (−22.6) and BNSS total (−11.3) scores. The most frequently reported adverse events (= 5%) were schizophrenia, headache, insomnia and anxiety. SEP−363856 had minimal effects on weight, lipids, glycemic indices, prolactin, and was associated with minimal risk of extrapyramidal symptom. Funding: Sunovion Pharmaceuticals Inc.